Exploring the Acoustic Physics of Speech Sounds in Phonetics - Kuchkorov Akhlidin Mirzokhid ugli; Xolmatov Doston Abdujabbor ugli (International Journal on Orange Technologies, 2023)
This study investigates the frequency, amplitude, and duration characteristics of sounds in phonetics and their implications for speech production and perception. Through a comprehensive analysis of speech data, including acoustic measurements and phonetic transcription, the study explores the acoustic properties of speech sounds across languages and dialects. The frequency analysis reveals distinct formant frequencies associated with vowel height, backness, and consonant characteristics such as broad spectra in fricatives and transient bursts in plosives. Amplitude analysis highlights differences between vowels and consonants, with vowels generally exhibiting higher amplitudes and conveying emphasis and stress. Duration analysis shows that vowels have longer durations compared to consonants, with variations based on stress and syllable timing patterns. The findings provide valuable insights into the production, transmission, and perception of speech sounds, contributing to our understanding of phonetic inventories, language-specific patterns, and speech perception models. Further research is needed to expand the investigation to diverse languages and dialects to enhance our understanding of the acoustic properties of sounds in phonetics and their linguistic variations.